Toward querying the national peril of kidnapping in Nigeria - Funmilayo Idowu Agbaje (Insights into Regional Development, 2022)
In Nigeria, the dynamics of kidnapping is framed in complexities. There are different types of kidnapping going on within the country ranging from resource-based kidnapping to political kidnapping and terrorist-based kidnapping (Agbaje, 2020; Onduku, 2011). While some are based on agitations for political and economic recognition, others are based on the need for compulsory recruitment by insurgents and terrorists. Existing gaps in the literature are demanding urgent attention from researchers and policymakers. This paper focuses on the need to look into the recent sporadic kidnappings in contemporary Nigeria to project sustainable solutions for them. This paper relies solely on secondary sources of data for its analysis. The paper concludes that a viable solution to the kidnapping problem in Nigeria depends mainly on full recognition of all forms of kidnapping in the country while strategically addressing them.